Trends in statin prescription prevalence, initiation, and dosing: Hong Kong, 2004–2015. (January 2019) - Blais, Joseph E.; Chan, Esther W.; Law, Sharon W.Y.; Mok, Michael T.; Huang, Duo; Wong, Ian C.K.; Siu, Chung-Wah
Abstract: Background and aims: Clinical practice guidelines recommend specific statin doses for the primary and secondary prevention of cardiovascular disease. Little is known about how statin utilization and dosing have evolved over time in Hong Kong. The aim of this study was to describe trends in statin prevalence, initiation, and dosing from 2004 to 2015. Methods: Patients receiving public health services, who were prescribed a statin, were included if they received a lipid test at a single center (n = 58, 672). Using the territory-wide electronic health record, prescribed daily statin dose, nondaily dose frequency, and statin dose intensity were determined for statin prescriptions from 2004 to 2015. Statin prescription prevalence and initiation rates were estimated using the appropriate at-risk population in the hospital catchment area as the denominator. Prescribed daily doses were stratified by primary or secondary cardiovascular prevention status to assess changes in statin dosing over time. Results: The prescription prevalence of statins was higher in 2015 (8.68%; 95% CI, 8.60%–8.75%) as compared with 2004 (1.82%; 95% confidence interval [CI], 1.78%–1.86%). Initiation rates for new statin users increased from 2004 to 2013. High-intensity statins were infrequently prescribed. New users generally had higher statin initiation rates for primary prevention. There were small increases in the prescribed daily doses of statins. Nondaily statin dosing was infrequent (0.42% of all prescriptions). Conclusions: The prevalence and initiation of statin prescriptions increased in Hong Kong, and was in part driven by low-intensity statins for the primary prevention of cardiovascular disease. Graphical abstract: Highlights: Prevalence of statin prescriptions was almost five times higher in 2015 versus 2004. Greater initiation of statins for primary prevention, especially since 2007. Initiation of high-intensity statins is uncommon in Hong Kong. Patients aged 70–84 years had the highest annual statin initiation rates.